Plantar pressure in athletes with chronic ankle instability during single-leg landings at different heights - Wang, Ansheng; Zhang, Qiang; Li, Chengjun; Tian, Zhibo; Zhang, Xinxin; Sun, Yuliang (Frontiers in Bioengineering and Biotechnology, 2025)
BackgroundDuring landing, athletes with Chronic Ankle Instability (CAI) often display abnormal ankle joint movements, and changes occur as the height increases. There is a lack of sufficient research on assessing foot pressure distribution during landing at different heights for athletes with CAI, which would help determine their injury risk.MethodsTwenty male athletes with CAI and twenty healthy controls were recruited in a 2 (group: CAI vs. healthy) × 2 (height: 30 cm-vs. 40 cm) mixed experimental design. A 2 × 2 mixed-design ANOVA was used to evaluate the foot pressure distribution characteristics during landing, measured using a 400 × 400 mm FreeMed baropodometric platform.ResultsInteraction effects were detected in peak force: metatarsal head 3 (MH3) (p = 0.047); load percentage: toes 2–5 (T2–5) (p = 0.050), MH3 (p = 0.038), rearfoot lateral (RF_L) (p = 0.045); peak pressure: MH3 (p = 0.013). Group effects were detected in peak force: T2–5 (p < 0.001), metatarsal head 4 (MH4) (p < 0.001), midfoot lateral (MF_L) (p < 0.001), and RF_L (p < 0.001); load percentage: MH4 (p < 0.001), MF_L (p < 0.001); peak pressure: T2–T5 (p = 0.001), MH4 (p < 0.001), MF_L (p < 0.001), and RF_L (p = 0.033); vCOP (p = 0.018). Pairwise comparisons showed that the peak force, pressure, and load distribution of athletes with CAI in T2–5, MH3, MH4, MF_L, and RF_L were significantly higher than those of the healthy group (p < 0.05). Additionally, the load percentage in RF_L and vCOP of athletes with CAI at a height of 40 cm was significantly greater than that of the healthy group (p < 0.05).ConclusionCompared with healthy individuals, athletes with CAI have increased peak forces, pressures and load percentage at the T2–5, MH3, MH4, MF_L and RF_L during landing. The load percentage in RF_L and vCOP of athletes with CAI increases as the height increases, reflecting impaired postural control and a higher risk of re-injury. This highlights the need for trainers to design specific training programs based on the distribution characteristics of foot pressure during landing exercises.